FOREIGN LANGUAGE TEACHING IN SPECIAL DIRECTIONS - Erkinov Adham Anvar o‘g‘li,; Abdullayeva Zarina,; Abdullayeva Zarina, (TADQIQOTLAR, 2026)
Annotation.  This  article  examines  the  methodologies  and  importance  of teaching foreign languages within special directions, focusing on English for Specific Purposes  (ESP).  Traditional  language  instruction  often  fails  to  address  the  unique communicative  needs  of  specialized  professional  fields.  This  paper  analyzes  how integrating student-centered strategies—such as needs analysis, task-based learning, and  authentic  materials—enhances  professional  linguistic  competence  and  student motivation.